Characteristic and Antibacterial Activity Test of Red Betel Leaf Essential Oil Against Propionibacterium Acne Bacteria - Bangkit Riska Permata; Kharisma Jayak Pratama; Mei Ika Nurul Khotimah; Sabrina Karim (Global Health Science Group, 2023)
Many Indonesian plants have the potential to have anti-acne activity, one of which is the red betel plant. Red betel leaf (Piper crocatum) contains flavonoids, alkaloids, tannins, and essential oils which are thought to be used as antimicrobials. The purpose of this study was to test the quality characteristics and test the antibacterial activity of red betel leaf essential oil against Propionibacterium acne bacteria. This research was an experimental study by identifying the physical quality and testing the antibacterial activity of the essential oil. human senses with the results of the smell or aroma obtained, namely the strong or stinging characteristic odor of red betel. The color of the essential oil obtained was yellow with a little brownish, bitter taste, the pH obtained from the essential oil was 4.65, the specific gravity of red betel leaf essential oil was 0.739, the ethanol soluble test obtained from the essential oil completely dissolved and white clear in a quantity of alcoholic solution. Antibacterial activity test results with red betel leaf essential oil concentrations of 5%, 10%, and 20%, could inhibit antibacterial of 7.16 mm, 10.3 mm, and 11.6 mm.